Comparative analysis of virulence-associated genes in ESBL-producing Escherichia coli isolates from bloodstream and urinary tract infections - Tanaka, Mayuko; Hanawa, Tomoko; Suda, Tomoya; Tanji, Yasunori; Minh, Le Nhat; Kondo, Kohei; Azam, Aa Haeruman; Kiga, Kotaro; Yonetani, Shota; Yashiro, Ryu; Ohmori, Takuya; Matsuda, Takeaki (Frontiers in Microbiology, 2025)
The prevalence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) is a global health concern due to the multidrug antimicrobial resistance in extraintestinal pathogenic E. coli (ExPEC). ExPEC causes severe infections such as bloodstream infections, meningitis, and sepsis. Uropathogenic E. coli (UPEC), a subset of ExPEC, is responsible for urinary tract infections (UTIs), ranging from asymptomatic bacteriuria and cystitis to more severe conditions, such as pyelonephritis, bacteremia, and sepsis (urosepsis). Although ESBL-producing E. coli may have a significant impact on patient outcomes, comparisons of genotype and virulence factors between ESBL-producing and non-ESBL-producing E. coli have not fully elucidated the factors influencing its pathogenicity. Therefore, in the present study, we analyzed the genotypes and virulence-associated genes of ESBL-producing strains isolated from the blood of patients with UTIs to determine the characteristics of ESBL-producing UPEC strains associated with severe infections. Most of the clinical isolates belonged to phylogroup B2, with the exception of three strains from phylogroup D. The MLST was ST131, followed by ST73, ST95, and ST38, which are commonly found in UPEC strains. Intriguingly, ST131 strains were associated with fewer sepsis cases compared to non-ST131 strains (8 of 38 cases by ST131 and 5 of 8 cases by non-ST131 [OR, 0.16; 95% CI, 0.038–0.873; p = 0.031]). In silico analysis of 23 clinical isolates revealed that the genes detected in all strains may play a significant role in the pathogenesis of invasive UTIs. Clustering and gene locus analysis highlighted the genotype-MLST dependence of UPEC-specific virulence-associated genes. ST38-specific strains were atypical, characterized by the absence of several UPEC-specific genes, including pap loci, pathogenicity island marker (malX), and ompT, as well as the presence of genes encoding Ycb fimbriae and a Type 3 secretion system, which are typically found in enteropathogenic E. coli (EPEC). These results suggest that the virulence of clinical isolates causing invasive infections can vary, and that the pathogenicity of UPEC should be considered when analyzing the correlation between MLST and the repertoire of virulence-associated genes.